Benchmarking and Strategic Analysis of Metro System; Enhancing Sustainability and Efficiency - Subedi, Pradip (Journal on Transportation System and Engineering, 2026)
With the growth of urbanization and demands towards sustainability in transportation, metropolitan systems are becoming vital elements of infrastructure in modern cities. The current study is aimed at conducting a benchmarking analysis of 47 metropolitan systems worldwide regarding the two sustainability dimensions, energy efficiency, and indoor air quality (IAQ).The research utilizes such statistical methods as correlation analysis, multiple regressions, and Monte Carlo simulations to analyze the impact of various operating parameters like the number of lines, stations, vehicles, length of the network and number of passengers on energy consumption and PM2.5 concentration. To enhance comparison of metropolitan systems, energy consumption indicators were assessed based on normalization. Based on the findings, there is a high positive correlation between the intensity of operations and total energy usage, with vehicle fleet (r = 0.9738) and vehicle kilometers (r = 0.9404) being the most influential variables. Metro systems with a larger capacity, for instance, Tokyo (95,798 GWh per year), have a higher demand for total energy because of the extent of the operation and high passenger numbers. This does not imply inefficiency but the sheer size of the metro system. Smaller metro systems use fewer amounts of energy, whereas some systems, like Singapore, provide relatively good air quality (PM₂.₅ = 24.5 µg/m³). A significant difference in the PM₂.₅ index was noted among different metro systems, with higher values in cities like Barcelona (102 µg/m³) and Beijing (163 µg/m³). Observations from real-world examples of metro systems like Santiago, Amsterdam, and Paris have pointed out the success of various strategies, which include incorporating renewable energy sources, regenerative brakes, and effective ventilation. According to simulations, policy instruments can help stabilize energy consumption and bring down air pollution levels, as seen in the metro system of Sydney. The analysis concludes that there are certain factors that determine whether a metro system is sustainable. These include the size of the system, intensity of operations, and environmental conditions, among others.